2021
DOI: 10.7150/thno.54066
|View full text |Cite
|
Sign up to set email alerts
|

Balancing the stability and drug activation in adaptive nanoparticles potentiates chemotherapy in multidrug-resistant cancer

Abstract: Rationale: Prodrug strategies that render the drug temporarily inactive through a cleavable linkage are able to modulate the physicochemical properties of drugs for adaptive nanoparticle (NP) formulation. Here we used cabazitaxel as a model compound to test the validity of our “balancing NP stability and specific drug activation” strategy. Methods: Cabazitaxel is conjugated to hydrophobic polylactide fragments with varying chain lengths via a self-immol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…To further elucidate the uptake mechanism, different inhibitors that specifically target endocytosis pathways were examined [ 39 ]. When A549 cisR cells were pretreated with chlorpromazine, an inhibitor of clathrin-mediated endocytosis, flow cytometry analysis showed that the cellular uptake of the NC was substantially decreased by ~ 40% compared to that of the untreated cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To further elucidate the uptake mechanism, different inhibitors that specifically target endocytosis pathways were examined [ 39 ]. When A549 cisR cells were pretreated with chlorpromazine, an inhibitor of clathrin-mediated endocytosis, flow cytometry analysis showed that the cellular uptake of the NC was substantially decreased by ~ 40% compared to that of the untreated cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As depicted in Fig. 4i and j, the administration of chlorpromazine (clathrin-dependent endocytosis inhibitor) signicantly decreased the cellular uptake of liposomes (reduction to 9.4 AE 0.05%), while cytochalasin D (pinocytosis inhibitor) and lipin (caveolin-mediated endocytosis inhibitor) [29][30][31] did not affect the internalization of DiI/SN38@LP. The FCM analysis presented in Fig.…”
Section: Cellular Uptake and Uptake Mechanism Of Sn38 Prodrug-based Liposomesmentioning
confidence: 89%
“…Formulating drugs into prodrugs by introducing covalent and coordinate bonds holds great promise to improve drug loading and self-assembly capabilities [ 18 , 19 ]. Recently, prodrug-based nano-DDS have integrated the advantages of both prodrug strategy and biomedical nanotechnology, attracting tremendous scientific interest [ 20 , 21 ]. Particularly, small-molecule prodrug-based nanoassemblies, as both carriers and cargos, are characterized by distinct high drug-loading (>50%, w / w ), accurate dosages, superior self-assembly properties and reduced excipient-related toxicity, showing more potential in cancer chemotherapy [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%